Theological Education as Missional Formation - George, Samuel (International review of mission, 2019)
Theological education is missional in nature. The disability perspective within theological education provides this missional aspect, which is vital for the growth and sustenance of the church. Since its inception, the World Council of Churches Ecumenical Disability Advocates Network (WCC-EDAN) has contributed to this great mission. This paper is an attempt to understand theological education as missional formation from the perspective of disability studies, especially the contributions of WCC-EDAN.